The effect of compensation, leadership style, leader-member exchange, and organizational citizenship behavior on performance - Sahyunu (Enrichment : Journal of Management, 2023)
This study aimed to examine and analyze the effect of compensation, leadership style, Leader-Member Exchange, and Organizational Citizenship Behavior on performance. This research was conducted at the Kendari Police Traffic Unit Police. The population used was 82 members of the Kendari Police Traffic Unit. Data collection is done through interviews. The analytical tool used is multiple linear regression techniques. The analysis results show that compensation has a positive and significant effect on performance, and leadership style has a positive but not significant impact on performance. It shows how leadership style is not related or not substantial to the version of members of the Kendari Police Traffic Unit. It is associated with the performance of members of the Kendari Police Traffic Unit, who need authoritarian support and cannot be involved in the decision-making process. Positive and significant compensation variables on performance. It shows that reasonable and proper assistance needs to be given to members of the Kendari Police Traffic Unit Police, and the need for employees will increase significantly. Leader-Member Exchange has a positive and significant effect on performance. Organizational Citizenship Behavior affects performance